2012
DOI: 10.1007/s00167-012-2305-y
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term survival following primary hinged total knee replacement is good irrespective of the indication for surgery

Abstract: Prospective cohort study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
0
21
1
Order By: Relevance
“…A study from the NJR (Baker et al. 2014) found that the implant survival for hinged knee replacements was comparable to conventional knee replacements, in contrast to our study, whereas others found the risk of revision to be higher in constrained primary implants (Moussa et al. 2017).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…A study from the NJR (Baker et al. 2014) found that the implant survival for hinged knee replacements was comparable to conventional knee replacements, in contrast to our study, whereas others found the risk of revision to be higher in constrained primary implants (Moussa et al. 2017).…”
Section: Discussioncontrasting
confidence: 78%
“…2017), but the rates of failure leading to revision surgery have previously only been evaluated in 1 registry study to our knowledge (Baker et al. 2014). Due to the limited use of these implants and the heterogeneity of the studies, it is difficult to obtain certain conclusions regarding the long-term results.…”
mentioning
confidence: 99%
“…Hinged implants used for primary TKA failed mostly due to infection (49.1%) and periprosthetic fracture (15.8%) (►Table 8). [90][91][92][93][94] The incidence of infection was relatively higher than that for the PS and VVC implants. It is difficult to determine whether this occurred due to the higher baseline comorbidities in these patients or due to flaws in the implant design.…”
Section: Hinged Implantsmentioning
confidence: 99%
“…Different results have been reported with the hinged knee prosthesis in the literature [ Table 4 ] 22 23 24 25 26 27 28 29 and the overall results were low for fixed hinged knee prosthesis. 30 Although the results of rotating type hinge knee prosthesis were better, the followup periods were short and the design of the prosthesis was different.…”
Section: Discussionmentioning
confidence: 99%